Livestock Asia: A strategy and action plan for research for poverty reduction - International Livestock Research Institute (International Livestock Research Institute, 2007)
This strategy and action plan has been co-produced by over 50 organizations and individuals. We hope that it will be of value to all those interested in reducing poverty through livestock research and development in South and South-East Asia and China. In particular we hope that it will be used by researchers, policymakers, aid specialists and development practitioners to inform the development of their policies, programs and projects.